ANALISIS ORGANOLEPTIK BEBERAPA MENU BREAKFAST MENGGUNAKAN PANGAN LOKAL TERHADAP PEMENUHAN KEBUTUHAN GIZI SISWA SEKOLAH DASAR - Henry S. Imbar; Vera T. Harikedua; Rivolta G.M. Walalangi (Jurnal GIZIDO, 2016)
School age children often skip breakfast for various reasons eg to rush off to school. Children whodo not eat breakfast, less task that requires concentration in class, often have values lower examresults, have limited memory and often absent. Breakfast effect on concentration and learningachievement of school children where there is a real difference of concentration ability usingsymbol-digit test between ordinary child breakfast with unusual breakfast. Results of other studiesshowed no significant relationship between energy intake breakfast with a concentration in school.Diversification of food consumption will provide encouragement and incentives on the supply offood products are more diverse and safe for consumption, including food products based on localresources.Organoleptic testing is a test that is based on sensing process. Sensing can also mean mentalreactions (sensation) if the senses receive stimuli (stimulus). Reaction or impression that is causeddue to the stimulation may be an attitude to toward or away from, liking or disliking objects willcause stimulation.Formulation of the problem in this research is how the acceptance andpreference level of primary school students towards some kind of breakfast menu using local foodin North Sulawesi in order to fulfill nutritional needs.The general objective of this study is to make local food in North Sulawesi as a basic ingredient inmaking a breakfast menu with a variety favored by children in order to fulfill the nutritional needs ofelementary school.The benefits of this research provide understanding to the community inparticular who have children of primary school age that the fulfillment of nutrients on elementaryschool children is not always synonymous with foodstuffs are expensive, must be imported, instant,branded, but the quality and nutritional content is not very relevant to the needs child nutrition.This type of research is quasy Experiment was conducted in a laboratory study Culinary NutritionPoltekkes Kemenkes Manado and Elementary School 06, which is located in Manado City.Collecting data in this study is the result of tests performed on the organoleptic properties, whichconsist of preference for appearance, flavor, texture, color and aroma. Hedonic data processingusing Kruskal Wallis test showed no significant difference from the third menu tested.Conclusion statistically no significant difference between the three breakfast menu with aconventional menu, but based on the average value of the hedonic score differences.